Insurance and sectorial growth nexus: Evidence from a developing economy - Yakubu Awudu Sare; Andrew Osei Agyemang; Emmanuel Caesar Ayamba; Bernard Bawuah; Akua Gyaawa Koranteng (Cogent Economics & Finance, 2023)
The insurance industry plays a substantive vitality in the growth of the economy. However, there is limited literature on the activities of the insurance industry and economic growth in Ghana. As one of the fastest-growing economies in sub-Saharan Africa before the global pandemic in 2020, there is a need to investigate the factors that influence the growth of the economy, of which insurance cannot be underscored. Moreover, proxies used to measure insurance for developing economies combined life insurance (LI) and non-life insurance (NLI) as one indicator. Also, none of the earlier studies considered the impact of insurance on sectorial growth in Ghana. Hence, this study relies on methodological innovation to fill in the literature gap. We employed time-series data from 1989 to 2022. From the Autoregressive Distributed Lag Analysis, an affirmative link was seen between LI and sectorial growth in both short-term and long-term period. With regards to the link between NLI and sectorial growth, except for service sector which revealed a positive but insignificant association, the other variables revealed an affirmative link between NLI and sectorial growth for both short term and long term. The findings affirm that NLI contributes significantly to the three sectors of the economy than LI. In addition, the findings confirm that the activities of insurance in the service sector of the economy are much more enormous than that of the industry and agricultural sectors.
Keywords: G22; G29; 330; Developing economy; economic growth; insurance; sectorial growth